Single-operator holmium laser lithotripsy under direct peroral cholangioscopy using an ultra-slim upper endoscope in a patient with a large stone in the common bile duct - Di Mitri, Roberto; Mocciaro, Filippo (Turkish Journal of Gastroenterology, 2017)
Abstract In patients with complicated stones (e.g., large stones) in the common bile duct (CBD), advanced treatment modalities are generally needed. Here we present an interesting case of a large CBD stone treated with holmium laser lithotripsy, which was performed under direct peroral cholangioscopy using an ultra-slim endoscope. An 86-year-old woman underwent endoscopic retrograde cholangiopancreatography for a symptomatic large CBD stone. After the failure of sphincterotomy, balloon sphincteroplasty, and mechanical and extracorporeal shock wave lithotripsy, we attempted to fragment the stone by peroral cholangioscopy using the holmium laser system through the operating channel of an ultra-slim endoscope. No complication was observed at the end of this procedure. Thus, holmium laser lithotripsy under direct peroral cholangioscopy performed using an ultra-slim endoscope is a feasible and safe endoscopic method for removing large CBD stones. Cite this article as: Di Mitri R, Mocciaro F. Single-operator holmium laser lithotripsy under direct peroral cholangioscopy using an ultra-slim upper endoscope in a patient with a large stone in the common bile duct. Turk J Gastroenterol 2017; 28: 505-9.